Teaching Clinical Laboratory Science As Part of a Science, Technology, Engineering, Mathematics and Health Program to Blind and Vision-Impaired Students. - Perkins, Lisa; Jamerson, Melissa (Clinical Laboratory Science)
The Virginia Commonwealth University School of Allied Health Professions collaborated with the Virginia Rehabilitation Center for the Blind and Vision Impaired to offer a program for blind and vision impaired 11th and 12th grade high school students. The program, known as the Learning Excellence in Academics Program (LEAP), provides these students the opportunity to participate in college-level courses. The purpose of LEAP is to determine the level of college-readiness skills these students possess along with familiarizing them to the demands of campus life. VCU's SAHP selected the Clinical Laboratory Science Department to teach the Introduction to Science course for the program. The CLS department's role was to introduce Science, Technology, Engineering, Mathematics and Health (STEM-H) curriculum to these students with disabilities. The CLS department utilized mobile devices and iCloud technology to facilitate teaching and encourage independent learning. The CLS faculty designed laboratory procedures focusing on sense of touch to safely incorporate laboratory sessions into the curriculum. A survey to assess outcomes was used to address college-readiness, comfort-level in a laboratory setting, effectiveness of available technology and interest in healthcare professions. In addition, the challenges faced and how they were overcome by the CLS department in presenting the main disciplines of clinical laboratory science through didactic and laboratory instruction in this unique population of STEM-H interested students will be discussed.